The effect of bank monitoring on loan repayment - Nicola Branzoli; Fulvia Fringuellotti (Federal Reserve Bank of New York, 2020)
Monitoring is one of the main activities explaining the existence of banks, yet empirical evidence about its effect on loan outcomes is scant. Using granular loan-level information from the Italian Credit Register, we build a novel measure of bank monitoring based on banks' requests for information on their existing borrowers and we investigate the effect of bank monitoring on loan repayment. We perform a causal analysis exploiting changes in the regional corporate tax rate as a source of exogenous variation in bank monitoring. Our identification strategy is supported by a theoretical model predicting that a decrease in the tax rate improves bank incentives to monitor borrowers by increasing returns from lending. We find that bank monitoring reduces the probability of a delinquency in a substantial way and that the effect is stronger for the types of loans that benefit most from bank oversight, such as term loans.
Keywords: G21; G32; H25; H32; 330; bank monitoring; nonperforming loan; tax policy